DEVELOPING ANALOG AND DIGITAL ELECTRONIC MEDIA KITS FOR AUTOMOTIVE ENGINEERING EDUCATION STUDENTS - Siswanto, Ibnu; Prasetyono, Agus Puji; Sudarwanto, Sudarwanto; Purwanto, Purwanto; Rudiyanto, Atha Fawwaz (Jurnal Pendidikan Teknik Mesin, 2024)
Instructional media has an important function for facilitating academia to achieve the learning objectives. Therefore, this study aims to develop an instructional media of the analog and digital electronics for automotive engineering education students. This study used a research and development method which consisting of 4D steps (define, design, development, and dissemination). The instructional media feasibility assessment from the lecturers and students was obtained using a questionaire. The lectures and students, after assessing the media kits, both were suggested that it has a good lay out, appropriate with the learning outcomes, and feasible for benefitting university learners in analog and digital electronics course especially in practice courses. The implementation of this analog and digital electronic media improves the students achievement in the basic analog and digital automotive electronics courses